Regulation of endothelial progenitor cell functions during hyperglycemia: new therapeutic targets in diabetic wound healing - Wan, Gui; Chen, Yangyang; Chen, Jing; Yan, Chengqi; Wang, Cheng; Li, Wenqing; Mao, Renqun; Machens, Hans-Günther; Yang, Xiaofan; Chen, Zhenbing (Journal of molecular medicine (Berlin, Germany), 2022)
Diabetes is primarily characterized by hyperglycemia, and its high incidence is often very costly to patients, their families, and national economies. Unsurprisingly, the number and function of endothelial progenitor cells (EPCs) decrease in patients resulting in diabetic wound non-healing. As precursors of endothelial cells (ECs), these cells were discovered in 1997 and found to play an essential role in wound healing. Their function, number, and role in wound healing has been widely investigated. Hitherto, a lot of complex molecular mechanisms have been discovered. In this review, we summarize the mechanisms of how hyperglycemia affects the function and number of EPCs and how the affected cells impact wound healing. We aim to provide a complete summary of the relationship between diabetic hyperglycosemia, EPCs, and wound healing, as well as a better comprehensive platform for subsequent related research.